UPAYA MENINGKATKAN KETERAMPILAN SISWA DALAM MEMAHAMI MATERI HAK DAN KEWAJIBANKU MENGGUNAKAN MODEL PJBL DENGAN PROJEK DESAIN POSTER PADA SISWA KELAS IV SD - Nabila, Putri; Nurjannah; Faisal Husna; Sukmawarti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is a classroom action research consisting of planning, acting, observing, and reflecting. The actions are carried out in two cycles, and each cycle consists of two meetings. By using the PJBL model with a poster design project on the material of rights and obligations at home and at school, there has been an increase in terms of learning outcomes and skills in doing assignments. This is evidenced by the results of the research cycle I meeting II by making a poster design project for rights and obligations has reached 85% in the very good category and the results of cycle II meeting II percentage 82% for LKPD while 91% for test questions this percentage is included in the very good category.